Mitochondrial extracellular vesicles, autoimmunity and myocarditis - Di Florio, Damian N.; Beetler, Danielle J.; McCabe, Elizabeth J.; Sin, Jon; Ikezu, Tsuneya; Fairweather, DeLisa (Frontiers in Immunology, 2024)
For many decades viral infections have been suspected as ‘triggers’ of autoimmune disease, but mechanisms for how this could occur have been difficult to establish. Recent studies have shown that viral infections that are commonly associated with viral myocarditis and other autoimmune diseases such as coxsackievirus B3 (CVB3) and SARS-CoV-2 target mitochondria and are released from cells in mitochondrial vesicles that are able to activate the innate immune response. Studies have shown that Toll-like receptor (TLR)4 and the inflammasome pathway are activated by mitochondrial components. Autoreactivity against cardiac myosin and heart-specific immune responses that occur after infection with viruses where the heart is not the primary site of infection (e.g., CVB3, SARS-CoV-2) may occur because the heart has the highest density of mitochondria in the body. Evidence exists for autoantibodies against mitochondrial antigens in patients with myocarditis and dilated cardiomyopathy. Defects in tolerance mechanisms like autoimmune regulator gene (AIRE) may further increase the likelihood of autoreactivity against mitochondrial antigens leading to autoimmune disease. The focus of this review is to summarize current literature regarding the role of viral infection in the production of extracellular vesicles containing mitochondria and virus and the development of myocarditis.